2021
DOI: 10.5194/acp-2021-694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: Photochemical production and loss rates of formaldehyde and ozone across Europe

Abstract: Abstract. Various atmospheric sources and sinks regulate the abundance of tropospheric formaldehyde (HCHO) which is an important trace gas impacting the HOx (≡ HO2 + OH) budget and the concentration of ozone (O3). In this study, we present the formation and destruction terms of ambient HCHO and O3 calculated from in-situ observations of various atmospheric trace gases measured at three different sites across Europe during summer time. These include a coastal site in Cyprus in the scope of the Cyprus Photochemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Many different methods enable the determination of the dominant chemical regime, such as the use of the weekend ozone effect, which considers the response of O 3 to NO x reductions on weekends, or the ratio of HCHO to NO 2 , with various approaches from in situ observations, remote sensing and model simulations (e.g., Jin et al, 2020;Pusede and Cohen, 2012;Nussbaumer and Cohen, 2020;Duncan et al, 2010). We have recently shown that the fraction α of methyl peroxyradicals (CH 3 O 2 ) forming formaldehyde (HCHO) in correlation with ambient NO concentrations is capable of indicating the dominant chemical regime based on three different field campaigns across Europe in Finland (HUMPPA 2012), Germany (HOPE 2012 and Cyprus (CYPHEX 2014) (Nussbaumer et al, 2021). CH 3 O 2 formed from, for example, the oxidation of acetaldehyde (CH 3 CHO) or methane (CH 4 ) can either react with NO or OH radicals to form HCHO or undergo the competing reaction with HO 2 to form methyl hydroperoxide (CH 3 OOH).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many different methods enable the determination of the dominant chemical regime, such as the use of the weekend ozone effect, which considers the response of O 3 to NO x reductions on weekends, or the ratio of HCHO to NO 2 , with various approaches from in situ observations, remote sensing and model simulations (e.g., Jin et al, 2020;Pusede and Cohen, 2012;Nussbaumer and Cohen, 2020;Duncan et al, 2010). We have recently shown that the fraction α of methyl peroxyradicals (CH 3 O 2 ) forming formaldehyde (HCHO) in correlation with ambient NO concentrations is capable of indicating the dominant chemical regime based on three different field campaigns across Europe in Finland (HUMPPA 2012), Germany (HOPE 2012 and Cyprus (CYPHEX 2014) (Nussbaumer et al, 2021). CH 3 O 2 formed from, for example, the oxidation of acetaldehyde (CH 3 CHO) or methane (CH 4 ) can either react with NO or OH radicals to form HCHO or undergo the competing reaction with HO 2 to form methyl hydroperoxide (CH 3 OOH).…”
mentioning
confidence: 99%
“…For more details, please see Fig. 1 in Nussbaumer et al (2021). α CH 3 O 2 consequently depends on the ambient concentrations of NO, OH and HO 2 and the respective rate constants for the reaction with CH 3 O 2 , the latter of which were taken from the IUPAC Task Group on Atmospheric Chemical Kinetic Data Evaluation (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al (2020); Pusede and Cohen (2012); Nussbaumer and Cohen (2020); Duncan et al (2010)). We have recently shown that the share α of methyl peroxyradicals (CH 3 O 2 ) forming formaldehyde (HCHO) in correlation with ambient NO concentrations is capable of indicating the dominant chemical regime based on three different field campaigns across Europe in Finland (HUMPPA 2012), Germany (HOPE 2012) and Cyprus (CYPHEX 2014) (Nussbaumer et al, 2021). CH 3 O 2 formed from e.g.…”
mentioning
confidence: 99%
“…the oxidation of methanol (CH 3 OH) or methane (CH 4 ) can either react with NO or OH radicals to form HCHO or undergo the competing reaction with HO 2 to form methyl hydroperoxide (CH 3 OOH). For more details, please see Figure 1 in Nussbaumer et al (2021). α CH3O2 consequently depends on the ambient concentrations of NO, OH and HO 2 and the respective rate constants for the reaction with CH 3 O 2 , the latter of which were taken from the IUPAC Task Group on Atmospheric Chemical Kinetic Data Evaluation (2021).…”
mentioning
confidence: 99%